Analysis of Effects of Kale Powder Consumption among Subjects with Potential Metabolic Syndrome: A Prospective Single-Arm Clinical Study - Tomomi, Ide; Asahi, Suzuki; Mihoko, Kurokawa; Naoto, Minagawa; Hisami, Inuzuka; Go, Ichien (Journal of Hypertension and Cardiology, 2016)
Objective: The prospective intervention study was conducted to investigate the effects of kale powder (Kale juice mixed with water or milk) consumption on metabolic syndrome in subjects with potential metabolic syndrome. Method: In Arita-cho, 149 male and female subjects with potential metabolic syndrome were instructed to consume kale powder for 8 weeks, and its effects on blood pressure, HbA1c, BMI, abdominal circumference, and blood triglycerides, LDL-C, HDL-C, and fasting blood sugar levels were assessed. Additionally, the safety of kale powder was examined. Results: After the 8-week long intake of kale powder, a significant decrease was observed in laboratory and home test-based blood pressure, abdominal circumference, and levels of LDL-C, HDL-C, and fasting blood sugar. Additionally, a hypotensive effect was observed on conducting stratified analysis, in which patients with blood pressure-related diseases were excluded. Furthermore, no safety concerns were identified regarding kale powder. Conclusion: Kale powder had a beneficial effect to maintain optimal blood pressure, blood sugar, and abdominal circumference in subjects with potential metabolic syndrome. Additionally, a hypotensive effect was observed within the normal range in subjects without blood pressure-related diseases.
Keywords: Brassica oleracea var acephala; Kale; Arita Health Cohort; Metabolic Syndrome; Blood Pressure